Nursery rhyme comics : 50 timeless rhymes from 50 celebrated cartoonists - McDonnell, Patrick, 1956- (New York : First Second, 2011)
Presents fifty traditional nursery rhymes in comic book format, with illustrations by well-known cartoonists.
Keywords: Nursery rhymes; Children's poetry; Graphic novels; Nursery rhymes; Graphic novels